Vincristine, Ifosfamide, and Doxorubicin for Initial Treatment of Ewing Sarcoma in Adults. (14th July 2017) - Wagner, Michael J.; Gopalakrishnan, Vancheswaran; Ravi, Vinod; Livingston, J. Andrew; Conley, Anthony P.; Araujo, Dejka; Somaiah, Neeta; Zarzour, Maria A.; Ratan, Ravin; Wang, Wei-Lien; Patel, Shreyaskumar R.; Lazar, Alexander; et al.
Abstract: Background: There are no clinical trials specifically addressing chemotherapy for adults with Ewing sarcoma (ES). Five‐year event‐free survival (EFS) of adults on pediatric studies of ES (44%–47%) is worse than that of children treated with the same therapy (69%). The object of this study was to review the results of therapy with vincristine, ifosfamide, and doxorubicin (VID) in the multidisciplinary treatment of adults with ES at our institution. Materials and Methods: Charts for adults treated for ES from 1995 to 2011 were retrospectively reviewed. Clinician‐reported radiographic tumor response, type of local therapy, pathologic response, and survival data were collected. Results: Seventy‐one patients were identified who received VID as initial therapy. The median age was 25 (range: 16–64). Forty‐two patients (59%) presented with a localized disease and 29 patients (41%) presented with a distant metastasis. Of all patients treated with VID, 83.6% showed a radiological response. Patients who presented with a localized disease had a 5‐year overall survival (OS) of 68% (median not reached), compared with 10.3% (median: 1.9 years) in those who presented with distant metastases. Five‐year EFS was 67%. The nine patients with a pelvic primary tumor had inferior 5‐year OS (42%) to the 33 with primary tumors at other sites (75%). The 5‐year OS of those who had greater than or equal to 95% necrosis after neoadjuvant VID ( n = 20; 5‐year OS: 84%) was superior to those who had less than 95% necrosis ( n = 13; 5‐year OS: 53%). Conclusion: In adults with primary ES, VID combined with an adjuvant strategy based on post‐treatment percent necrosis has favorable outcomes compared with historical adult controls. Abstract : Ewing sarcoma is rare in adults, and there are no dedicated clinical trials in the adult population. This article reviews the results of therapy with vincristine, ifosfamide, and doxorubicin in the multidisciplinary treatment of adults with Ewing sarcoma.